3=8y-15

Rewrite the equation as 8y-15=3.

8y-15=3

To remove the radical on the left side of the equation, square both sides of the equation.

8y-152=32

Multiply the exponents in ((8y-15)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(8y-15)12⋅2=32

Cancel the common factor of 2.

Cancel the common factor.

(8y-15)12⋅2=32

Rewrite the expression.

(8y-15)1=32

(8y-15)1=32

(8y-15)1=32

Simplify.

8y-15=32

Raise 3 to the power of 2.

8y-15=9

8y-15=9

Move all terms not containing y to the right side of the equation.

Add 15 to both sides of the equation.

8y=9+15

Add 9 and 15.

8y=24

8y=24

Divide each term by 8 and simplify.

Divide each term in 8y=24 by 8.

8y8=248

Cancel the common factor of 8.

Cancel the common factor.

8y8=248

Divide y by 1.

y=248

y=248

Divide 24 by 8.

y=3

y=3

y=3

Solve for y 3 = square root of 8y-15